Meningkatkan Kemampuan Membaca Al-Qur'an Siswa melalui Metode Ummi di MIS Bhakti Kota Padang - Nurmaita, Nurmaita; Nursiah, Nursiah; Nursakti, Nursakti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of the Ummi method in improving students' Qur'an reading skills at MIS Bhakti Kota Padang. The research employs a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of four stages in each cycle: planning, action implementation, observation, and reflection. The subjects of this study were third and fourth-grade students who struggled with Qur'an reading. Data collection techniques included pre-test and post-test assessments of Qur'an reading skills, observations of student engagement, and questionnaires to assess their responses to the applied method. Data were analyzed quantitatively using statistical tests to compare reading skill improvements across cycles and descriptively to evaluate experiences and challenges in implementing the Ummi method. The findings indicate that the Ummi method gradually enhances students' fluency and accuracy in reading the Qur'an. In the first cycle, student participation increased, though some still faced difficulties with pronunciation and tajweed. In the second cycle, students demonstrated significant improvements in fluency and comprehension. Additionally, questionnaire results revealed that most students felt more motivated and comfortable with the Ummi method compared to conventional approaches. However, challenges such as the need for more intensive teacher guidance and adaptation of teaching strategies should be addressed for optimal results.